Problematika Minimnya Sarana dan Prasarana mempengaruhi Proses Pembelajaran Disekolah 3T - Astuti, Nita; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine in depth the effect of the lack of facilities and infrastructure on the learning process in schools in disadvantaged, frontier, and outermost (3T) regions in Indonesia using the literature review method. This method is carried out through the analysis of various literature such as scientific journals, books, policy documents, and relevant previous research reports. The results of the study show that limited facilities and infrastructure, such as inappropriate classrooms, lack of learning media, and limited access to technology, have a significant effect on the low quality of the learning process. Teachers experience obstacles in implementing varied learning methods, while students show decreased motivation and learning outcomes. This study emphasizes the importance of equitable distribution of educational facilities and policy synergy between agencies to support the improvement of the quality of education in the 3T area.